Changes in the Level of Socio-Economic Development of Communes in the Lubelskie Voivodship - Jolanta Jóźwik; Grażyna Gawrońska (Barometr Regionalny)
The paper presents an attempt of determination of changes in the level of socio-economic development of communes in the Lubelskie Voivodship. The variability of socio-economic development for 2005 and 2015 was determined based on the measure of development proposed by Hellwig. The research covered 193 communes, including 166 rural communes and 27 urban-rural communes. The source material was data for the local level (i.e., communes) obtained from the Local Data Bank of the Central Statistical Office. The research showed that the Lubelskie Voivodship is characterized by relatively high internal socio-economic variability. High level of development was usually obtained for urban-rural communes and communes neighboring on urban communes. The lowest level was determined for communes characterized by peripheral location. The large majority of communes represented a moderate level of socio-economic development. An increase in the general level of socio-economic development was observed in 2015 in comparison to 2005 in the majority of communes of the Lubelskie Voivodship.